Pengembangan Evaluasi Pembelajaran Berbantuan Wordwall Materi Melaksanakan Pengurusan Jenazah Untuk Kelas 11 SMA Negeri 12 Luwu Utara - Andika, Putri Rahmadani; Fakhrunnisaa, Nur; Nursyamsi, Nursyamsi (ISLAMIKA, 2024)
The research discusses the instrument for developing learning evaluations assisted by wordwall material for carrying out corpse management for class Types of R&D (Research and Development) research, ADDIE model: Analysis (analysis), Design (design), Development (development), Implementation (implementation), Evaluation (evaluation). The subject is a class XI IPA student at SMAN 12 North Luwu. Observation data collection techniques, questionnaires and documentation. Data analysis techniques, qualitative descriptive analysis and quantitative descriptive analysis. The research results showed that media experts were 95% in the "very valid" category, language validation was 95% in the "very valid" category, and PAI learning evaluation expert validation was 92% in the "very valid" category. The practicality of the product is 89.2% in the "very practical" category. Based on this, a summary of the development of a learning evaluation instrument assisted by wordwall material for carrying out corpse management for class XI at SMAN 12 North Luwu, is suitable for use as an evaluation instrument.